Association of Fig Pollinating Wasps and Fig Nematodes inside Male and Female Figs of a Dioecious Fig Tree in Sumatra, Indonesia - Jauharlina; Oktarina, Hartati; Sriwati, Rina; Sayuthi, Muhammad; Kanzaki, Natsumi; Quinnell, Rupert J.; Compton, Stephen G. (Insects (Basel, Switzerland), 2022)
Nematodes can grow within the inflorescences of many fig trees (Ficus spp., Moraceae); however, the feeding behaviour of most nematodes is not known. Fig pollinating wasps (Hymenoptera: Agaonidae) transfer nematodes into young figs upon the wasps’ entry into the figs to deposit their eggs. Most Asian fig trees, however, are functionally dioecious, and the pollinating wasps that enter female figs are unable to reproduce. They fail to produce the offspring required to carry the new generations of nematodes. We examined whether female figs of F. hispida can nonetheless support the development of phoretic nematode populations. Nematodes were extracted from male and female figs sampled in Sumatra, Indonesia, to compare the growth of their populations within the figs. We found three species of nematodes that grew within figs of male and female trees of F. hispida: Ficophagus cf. centerae (Aphelenchoididae), Martininema baculum (Aphelenchoididae) and Caenorhabditis sp (Rhabditidae). The latter species (Caenorhabditis sp.) has never been reported to be associated with F. hispida before. Nematode populations peaked at around 120–140 individuals in both sexes of figs, at the time when a succeeding generation of adult fig wasps appeared within male figs. The female figs could support the growth and reproduction of the three nematodes species; however, the absence of vectors meant that female figs remained as traps from which there could be no escape.